Fat/carbohydrate ratio but not energy density determines snack food intake and activates brain reward areas - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (Scientific Reports, 2015)
The snack food potato chips induces food intake in ad libitum fed rats, which is associated with modulation of the brain reward system and other circuits. Here, we show that food intake in satiated rats is triggered by an optimal fat/carbohydrate ratio. Like potato chips, an isocaloric fat/carbohydrate mixture influenced whole brain activity pattern of rats, affecting circuits related e.g. to reward/addiction, but the number of modulated areas and the extent of modulation was lower compared to the snack food itself.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.fatcar

Identification of the oleic acide ethanolamide (OEA) isomer cis-vaccenic acid ethanolamide (VEA) as a highly abundant 18:1 fatty acid ethanolamide in blood plasma from rats and humans - Röhrig, Waldemar; Waibel, Reiner; Perlwitz, Christopher; Pischetsrieder, Monika; Hoch, Tobias (Analytical and Bioanalytical Chemistry, 2016)
The endocannabinoid system is important in various physiological pathways, especially the regulation of food intake. It consists of endocannabinoids like 2-arachidonoyl-glycerol (2-AG) or the fatty acid ethanolamide archachidonoyl-ethanolamide (AEA) with binding affinity to cannabinoid receptors. Further, fatty acid ethanolamides (FAEAs) influence the endocannabinoid system without affecting cannabinoid receptors by using independent physiological pathways. Among FAEAs, oleic acid ethanolamide (OEA) gained importance because of its promising ability to reduce food intake. By ultrahigh-performance liquid chromatography–electrospray ionization–tandem mass spectrometry (UHPLC–ESI–MS/MS), we detected a chromatographically separated molecule in plasma samples from rats and humans with identical mass and fragmentation patterns as those of OEA. Via synthesis and extensive analysis of ethanolamides of different cis/trans- and position isomers of oleic acid (cis9-18:1), we could identify the unknown molecule as vaccenic acid (cis11-18:1) ethanolamide (VEA). In this study we identified VEA as the most abundant 18:1 FAEA in rat plasma and the second most abundant 18:1 FAEA in human plasma.
Keywords: OEA; VEA; fatty acid ethanolamides; endocannabinoid system; LC - MS/MS

Manganese-Enhanced Magnetic Resonance Imaging for Mapping of Whole Brain Activity Patterns Associated with the Intake of Snack Food in Ad Libitum Fed Rats - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (PLoS ONE, 2013)
Non-homeostatic hyperphagia, which is a major contributor to obesity-related hyperalimentation, is associated with the diet's molecular composition influencing, for example, the energy content. Thus, specific food items such as snack food may induce food intake independent from the state of satiety. To elucidate mechanisms how snack food may induce non-homeostatic food intake, it was tested if manganese-enhanced magnetic resonance imaging (MEMRI) was suitable for mapping the whole brain activity related to standard and snack food intake under normal behavioral situation. Application of the MnCl2 solution by osmotic pumps ensured that food intake was not significantly affected by the treatment. After z-score normalization and a non-affine three-dimensional registration to a rat brain atlas, significantly different grey values of 80 predefined brain structures were recorded in ad libitum fed rats after the intake of potato chips compared to standard chow at the group level. Ten of these areas had previously been connected to food intake, in particular to hyperphagia (e.g. dorsomedial hypothalamus or the anterior paraventricular thalamic nucleus) or to the satiety system (e.g. arcuate hypothalamic nucleus or solitary tract); 27 areas were related to reward/addiction including the core and shell of the nucleus accumbens, the ventral pallidum and the ventral striatum (caudate and putamen). Eleven areas associated to sleep displayed significantly reduced Mn2+-accumulation and six areas related to locomotor activity showed significantly increased Mn2+-accumulation after the intake of potato chips. The latter changes were associated with an observed significantly higher locomotor activity. Osmotic pump-assisted MEMRI proved to be a promising technique for functional mapping of whole brain activity patterns associated to nutritional intake under normal behavior.

Non-homeostatic intake of snack foods: Molecular triggers and effects on brain activity pattern - Hoch, Tobias; Heß, Andreas; Pischetsrieder, Monika (The Chemical Sensory Informatics of Food: Measurement, Analysis, Integration, 2015)
Craving for special types of food like snack food can tremendously influence our energy balance. The result: obesity due to a non-homeostatic, hedonic food intake, i.e. an intake of energy independent of hunger and satiety. The intake of potato chips – an often craved highly palatable snack food – has a great influence on whole brain activity pattern. Especially the reward system as well as circuits regulating food intake, sleep and locomotor activity are affected. Furthermore, we could show that the fat and carbohydrate content is a main contributor to the palatability of potato chips. These first steps of the identification of the molecular triggers and the corresponding effects on brain activity pattern of the non-homeostatic intake of highly palatable snack food are reviewed in this chapter.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.nonhom

Snack food intake in ad libitum fed rats is triggered by the combination of fat and carbohydrates - Hoch, Tobias; Pischetsrieder, Monika; Heß, Andreas (Frontiers in Psychology, 2014)
Snack food like potato chips substantially contributes to energy intake in humans. In contrast to basic food, snacks are consumed additionally to other meals and may thereby lead to non-homeostatic energy intake. Snack food is also frequently associated with hedonic hyperphagia, a food intake independent from hunger. Analysis of brain activity patterns by manganese-enhanced MRI has previously revealed that the intake of potato chips in ad libitum fed rats strongly activates the reward system of the rat brain, which may lead to hedonic hyperphagia. The purpose of the present study was to develop a two-choice preference test to identify molecular determinants of snack food triggering extra food intake in ad libitum fed rats. Different kinds of test food were presented three times a day for 10 min each time. To minimize the influence of organoleptic properties, each test food was applied in a homogenous mixture with standard chow. Food intake as well as food intake-related locomotor activity were analyzed to evaluate the effects induced by the test foods in the two-choice preference test. In summary, fat (F), carbohydrates (CH), and a mixture of fat and carbohydrates (FCH) led to a higher food intake compared to standard chow. Notably, potato chip test food (PC) was highly significantly preferred over standard chow (STD) and also over their single main macronutrients F and CH. Only FCH induced an intake comparable to PC. Despite its low energy density, fat-free potato chip test food (ffPC) was also significantly preferred over STD and CH, but not over F, FCH, and PC. Thus, it can be concluded that the combination of fat and carbohydrates is a major molecular determinant of potato chips triggering hedonic hyperphagia. The applied two-choice preference test will facilitate future studies on stimulating and suppressive effects of other food components on non-homeostatic food intake. © 2014 Hoch, Pischetsrieder and Hess.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.snackf
Keywords: Eating behavior; Food intake; Macronutrients; Preference test; Rat; Snack food